Potassium channel-based optogenetic silencing - Yinth Andrea Bernal Sierra; Benjamin R. Rost; Martin Pofahl; António Miguel Fernandes; Ramona A. Kopton; Sylvain Moser; Dominik Holtkamp; Nicola Masala; Prateep Beed; John J. Tukker; Silvia Oldani; Wolfgang Bönigk; et al. (Nature Communications, 2018)
Optogenetic tools enable precise experimental control of the behaviour of cells. Here, the authors introduce a genetically-encoded two-protein system that enables silencing of excitable cells such as neurons and cardiomyocytes using blue light, and demonstrate its utility both in vitro and In vivo.